Water depth-dependent stem elongation of completely submerged Alternanthera philoxeroides is mediated by intra-internodal growth variations - Jing, Shufang; Ren, Xinyi; Lin, Feng; Niu, Hangang; Ayi, Qiaoli; Wan, Binna; Zeng, Bo; Zhang, Xiaoping (Frontiers in Plant Science, 2024)
Complete submergence, especially deep submergence, poses a serious threat to the growth and survival of plants. One study previously showed that Alternanthera philoxeroides (a herbaceous perennial plant) submerged at depth of 2 m presented fast stem elongation and reduced stem elongation as water depth increased. In the present study, we aimed to figure out from the morphological and anatomical perspective how the differential growth response of the plant to water depth was achieved.We investigated the elongation of different stem parts and the relationship of stem elongation to cell size and number in A. philoxeroides by conducting experiments using a series of submergence depths (0 m, 2 m, 5 m, and 9 m). The results showed that, in comparison with unsubmerged plants, completely submerged plants exhibited enhanced elongation at depths of 2 m and 5 m but suppressed elongation at depth of 9 m in immature stem internodes, and displayed very little elongation in mature stem internodes at any depths. The stem growth of A. philoxeroides at any submergence depth was chiefly caused by the elongation of the basal parts of immature internodes. The elongation of the basal parts of immature internodes was highly correlated to both cell proliferation and cell enlargement, but the elongation of the middle and upper parts of immature internodes correlated nearly only with cell enlargement. This study provided new information on the growth responses of A. philoxeroides to heterogeneous submergence environments and deepened our understanding of the growth performance of terrestrial plants in habitats prone to deep floods.